Effect of different temperatures on developmental periods and reproduction of fruit fly (Bactrocera cucurbitae) - Tamjida Islam Tora,; Md. Mamunur Rahman,; Mansura Afroz,; Md. Ramiz Uddin Miah,; Md Ruhul Amin,; Md. Humayun Kabir,; Md. Mizanur Rahman,; Jahidul Hassan,; Biswas, Jatish Chandra (Penerbit Universiti Kebangsaan Malaysia, 2023)
Considering the economic value of cucurbits and the crop losses due to fruit fly infestation, the current experiment was carried out in controlled laboratory conditions to investigate the effects of temperature on the growing durations and reproduction of fruit fly as a response to climate change. At first, the culture of cucurbit fruit fly (infested bitter gourd fruits) was collected from the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University and then the emerged larvae were artificially reared on bitter gourd slices under laboratory conditions at 25°C, 30°C and 35°C. Differences among the three tested temperatures for different developmental periods were significant, but the differences in male-female ratio at different temperatures were not statistically significant. The duration of life stages was significantly shorter when reared at high temperature (35°C) than when reared at low temperature (25°C). The incubation period and the durations of larval and pupal development of the insect decreased from 17.07±0.09 hours to 15.87±0.03 hours, 5.31±0.03 days to 3.40±0.08 days and 8.83±0.01 days to 8.08±0.04 days, respectively due to the increase of temperature from 25°C to 35°C. The mating duration, fecundity, hatching percentages were maximum at 25°C (3.54±0.01 days, 74.93±0.07 and 86.67±0.03%, respectively). Although some reproductive parameters were favored at 25°C, the results clearly indicate that an increase in temperature in the context of climate change would benefit the insect with more females and more generations per year due to having a short life cycl